Can anyone please help me find out the solution of this equation which came out as a result of Laplace's equation :
xy" + y' = cxy .........where c is a constant. or this one : x^2(y") + 2xy' = (cy)x^2 . ........again c is a constant.
Can anyone please help me find out the solution of this equation which came out as a result of Laplace's equation :
xy" + y' = cxy .........where c is a constant. or this one : x^2(y") + 2xy' = (cy)x^2 . ........again c is a constant.
These are Cauchy-Euler Equations.